Konstruksi Alat Ukur Kepemimpinan Spiritual dalam Keluarga - Hasna Esa Nisrina; Muhammad Irsyad Faruq; Rina Masruroh; Siti Sa'adah Nurlatifah; Siti Khairun Nisa (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2020)
This study aims to examine spiritual leadership in the context of the head of the family. The spiritual leadership concept is lifted from Fry (2003) which is defined as a matter that consists of values, attitudes, and behaviors needed to intrinsically motivate oneself or others so that they have a sense of survival through spiritual vocation and membership. The construct approach used is the modification approach. The number of samples in this study amounted to 405 subjects with purposive sampling. The content validation used is in the form of CFA. Of the five dimensions measured, there is one falling dimension in testing, namely the meaning dimension. The other four dimensions, namely vision, altruistic love, hope/faith, and membership, can be measured by 26 valid and reliable items based on the confirmatory factor analysis and Cronbach alpha test. Measuring instruments developed can be used again for further research.